Writing the world of policing: the difference ethnography makes - Fassin, Didier (The University of Chicago Press, 2017)
Introduction: ethnographying the police / Didier Fassin -- Position. Accountability: ethnographic engagement and the ethics of the police (United States) / Steve Herbert ; Complicity: becoming the police (South Africa) / Julia Hornberger ; Intimacy: personal policing, ethnographic kinship, and critical empathy (India) / Beatrice Jauregui ; Affect: the virtual force of policing (Taiwan) / Jeffrey T. Martin -- Observation. Predicament: interpreting police violence (Mozambique) / Helene Maria Kyed ; Morality: understanding police training on human rights (Turkey) / Elif Babul ; Experience: being policed as a condition of life (Chile) / Clara Han ; Aspiration: hoping for a public policing (Bolivia) / Daniel M. Goldstein -- Description. Sense and sensibility: crafting tales about the police (Thailand) / Duncan McCargo ; Detention: police discretion revisited (Portugal) / Susana Durao ; Alibi: the extralegal force embedded in the law (United States) / Laurence Ralph ; Boredom: accounting for the ordinary in the work of policing (France) / Didier Fassin